Community-Driven Nursing Interventions: Enhancing Prevention and Early Detection of Chronic Kidney Disease in Hypertensive Patients at Non-communicable Disease Clinics - Sumathi Arumugam; Theranirajan Ethiraj; Shankar Shanmugam Rajendran; Palani Tamilselvi; Umamaheswari Periyasamy; Ghercy Elumalai; Saranya Subbaiya (Journal of Pharmacy and Bioallied Sciences)
Background: Chronic kidney disease (CKD) is one of the global key health issues; hypertension continues to be among the leading risk factors. This, therefore, calls for early detection and prevention with the aim of reducing the disease’s progression and socioeconomic burden. It is through such community-based nursing interventions that the gap in prevention and early detection may be bridged. Aim: This study aims to assess the effectiveness of a community-based nursing intervention aimed at improving knowledge, attitudes, and practices (KAP) related to CKD prevention among hypertensive clients attending an non-communicable disease (NCD) clinic. Materials and Methods: Quasi-experimental design with 100 hypertensive clients purposively divided into experimental and control groups. The experimental group received community-based nursing interventions, which included educational sessions, whereas the control group received routine care. The pre- and post-intervention KAP were measured through structured questionnaires. Data analysis was set in SPSS version 22 and fixed at P ≤ 0.05. Outcome: Pre-intervention, both groups had poor knowledge and practices. Post-intervention, 68% of the intervention group showed adequate knowledge, and 66% displayed good practices, while no change was observed in the control group. Correlations were found between KAP score and demographics—age and BMI, in the intervention group. Conclusion: Community-based nursing interventions enhance KAP related to CKD prevention in hypertensive clients in an effective manner. Including these interventions in routine care will ultimately be cost-effective and crucial, mainly in low-resource environments.